Low Molecular Weight Antioxidant versus Flavonoids in Combating Oxidative Stress: Which One is Superior? - Taufiqurrachman Nasihun (Sains Medika, 2018)
According to the free radical theory of aging, firstly proposed by Denham Harman, the most prominent cause of aging and degenerative diseases (DD) is continuously chemical reaction in cells and tissues. In this context aging and or DD is manifested as chemical composition, whilst aging process is reflected by chemical reaction affected by environment (Harman, 1981). Thus, both aging and DD have similar process, predisposed with oxidative stress and characterized by the progressive cellular alteration accumulation in line with time and account for increase in susceptibility to diseases and death. The most prevalent chemical reaction is between free radical reactive oxygen species (ROS) and reactive nitrogen species (RNS) with cellular biomolecules such as lipids, protein, carbohydrate, and DNA (Lamichhane et al., 2013). In order to prevent the deleterious effect of that chemical reaction, human’s body provides an antioxidant defense system to counterbalance the free radical dangerous effect. However, owing to inappropriate life style, eating style, physical activity, and poor environment, production of ROS and RNS may be increased and induce cellular damages. Numerous publications indicated that oxidative stress and cellular damages can be reduced even prevented by exogenous antioxidant, thus intake antioxidant from external sources is necessary. There are two type of exogenous antioxidant consisting of low molecular weight antioxidant (LMWA) and flavonoids. Unfortunately, the effect of LMWA on delaying aging and ameliorating DD remain inconsistent. On the other hand, numerous data indicate that flavonoids a botanical antioxidant was capable of improving oxidative stress and emerging as an alternative promising antioxidant (Sudhakaran et al., 2019). However, the effect of LMWA and flavonoids in combating oxidative stress remain unknown which one is better.